SOME QUESTIONS OF GERMINATION’S BIOLOGY OF ASCLEPIAS SYRIACA L. SYS. A. CORNUTI DECNE - Папка, О. С. (Scientific Progress & Innovations, 2015)
The results of researches which testify that the seed germ of Asclepias syriaca L. sys. A. Cornuti Decne. through 1–1,5 month after collection is fully able to growth (terms for the germination of the freshly collected seeds are needed the same, as well as for those, that ripened) are presented. In un-optimal terms the freshly collected seeds germinate approximately similar, as well as ripened. It shows that the post-harvest ripening of seeds Asclepias syriaca L. sys. A. Cornuti Decne. are poorly expressed.